Who are Digital Immigrants? - Christopher Zwolenski (Adult Education Research Conference, 2010)
In short, the point I am making is that rejection of the philosophy and practice of traditional education sets a new type of difficult educational problem for those who believe in the new type of education. We shall operate blindly and in confusion until we recognize this fact; until we thoroughly appreciate that departure from the old solves no problems. (Dewey, 1938/1997, p. 25)